Synthesis a novel multilamellar mesoporous TiO2/ZSM-5 for photo-catalytic degradation of methyl orange dye in aqueous media - Znad, Hussein (Elsevuer BV, 2018)
TiO2 photocatalyst hybridized with new multilamellar vesicles (MLVs) mesoporous ZSM-5 substrate (TiO2/ZSM-5) were prepared by the direct templating technique for decolorization and minerlization of methyl orange (MO) dye effluent. The synthesized materials were characterized by X-ray diffraction (XRD), Field-emission scanning electron microscopy (FE-SEM), Fourier-transformed infrared spectroscopy (FTIR), and Brunauer-Emmett-Teller (BET). It was found that the specific surface area (SBET) of the synthesized TiO2/ZSM-5 was 1151 m2 g−1. The results also indicated that the zeolite structure conserves mesoporous structure after the removal of surfactant templates. Several parameters were also investigated such as the effect of catalyst types, pH, adsorption/photocatalysis phenomenon and contact time. Under 180 min solar irradiation, MO dye was efficiently decolorized and mineralized to be 99.55% and 99%, respectively, at an initial MO concentration of 20 mg L−1. Furthermore, the photocatalysis kinetic fit the pseudo-second-order model well and a great potential for saving energy associated with its recyclability. Therefore, the synthesized TiO2/ZSM-5 could be used as a promosing photocatalysis for fast removal and treatment of coloured wastewater.